Educação sexual na escola: normatividade, diversidade e perspectiva queer nas políticas públicas - Pais, Juan Barbosa. [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Esta dissertação investiga como os discursos sobre gênero e sexualidade se materializam nas políticas educacionais brasileiras. Com abordagem qualitativa, utiliza análise documental e revisão bibliográfica. Apoiada em autores como Judith Butler e Guacira Lopes Louro, examina como tais políticas tensionam reforçam normas de gênero e sexualidade no contexto escolar.

This dissertation investigates how discourses on gender and sexuality are materialized in Brazilian educational policies. Using a qualitative approach, it employs document analysis and literature review. Drawing on authors such as Judith Butler and Guacira Lopes Louro, it examines how these policies either challenge or reinforce gender and sexuality norms within the school context.
Sex education at school: normativity, diversity and queer perspective in public policies
Keywords: Educação; Política educacional; Educação e Estado; Gênero; Sexualidade; Queer; Education; Education and state; Queer theory